The Activities and Secretion of Cytokines Caused by Delamanid on Macrophages Infected by Multidrug-Resistant Mycobacterium tuberculosis Strains - Lyu, Xia-Li; Lin, Ting-Ting; Gao, Jing-Tao; Jia, Hong-Yan; Zhu, Chuan-Zhi; Li, Zi-Hui; Dong, Jing; Sun, Qi; Shu, Wei; Pan, Li-Ping; Zhang, Zong-De; Li, Qi (Frontiers in Immunology, 2021)
Background: Delamanid (Dlm) is an effective drug against drug-susceptible and drug-resistant Mycobacterium tuberculosis strains, including Multidrug-resistant Mycobacterium tuberculosis (MDR-MTB). There are few reports on the activity of Dlm on macrophages infected by MDR-MTB strains. Therefore, this article aims to observe the bactericidal activity of Dlm on macrophages infected by MDR-MTB strains and explore the cellular immune mechanism related to its bactericidal effect, so as to provide a basis for further perfecting the mechanism of Dlm. Methods: Samples were respectively collected to count the intracellular colony-forming unit (CFU) of macrophages infected by MDR-MTB or H37Rv strains at 4h, 8h, 24h and 48h after Dlm at MIC, 10MIC and 20MIC were administered and to detect the level of IL-12/23 p40, TNF-α, IL-6 and IL-10at 4h, 24h and 48h after Dlm at MIC were administered. Results: (1)After Dlm was applied to macrophages infected by MDR-MTB strains: 1) The intracellular CFU gradually decreased, reached the lowest value at 48h and was lower than that of Dlm before administration and infection group (P<0.05). 2) The intracellular CFU was further reduced after increasing Dlm dose to 10MIC and 20MIC. (2) 1) The level of IL-12/23 p40 at any time didn't change compared with that of Dlm before administration (P>0.05), while the level of IL-12/23 p40 at 4h was higher than that of the infection group (P<0.05). The level of TNF-α at 24h and 48h were higher than that of Dlm before administration (P<0.05). 2) The level of IL-6 at 24h and 48h were higher than that of Dlm before administration (P<0.05), and were lower than that of infection group (P<0.05). (3) The level of IL-12/23 p40 and IL-10 didn't change with the change of intracellular CFU (P<0.05), while the level of TNF-α and IL-6 increased with the intracellular CFU decreasing, and the increase level of TNF-α was lower than that of the infection group (P<0.05). Conclusions: Dlm had strong bactericidal activity against intracellular MDR-MTB which was time-dependent and concentration-dependent. Its bactericidal activity against intracellular MDR-MTB strains was weaker than that against H37Rv. Dlm might have immunomodulatory effect, inducing low expression of Th2 cytokines IL-6 and IL-10.